Cytostatic and cytotoxic effects of tyrphostin AG1296 on RMS cells - Lasota, Małgorzata; Klein, Andrzej; Balwierz, Walentyna (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : The aim of the work was to determine the influence of tyrphostin AG1296, an inhibitor of platelet-derived growth factor receptor (PDGFR) tyrosine kinase, on autocrine growth of rhabdomyosarcoma (RMS) cells. Materials and methods : RMS cells were cultured in serum-free DMEM/F12 medium. Modified crystal violet (CV) and MTT methods were used to determine the RMS cells’ proliferation and viability. Influence of the investigated inhibitor on cell apoptosis or necrosis was determined by differential staining with Hoechst No. 33258 and propidium iodide. Results : The AG1296 inhibitor affects RMS cell proliferation in a dose-dependent way at the concentration range 1–100 µM. At concentrations above 25 M there was 100% inhibition of growth of these cells and a cytotoxic effect was noticed. 50% inhibition of RMS cells proliferation (IC50) was observed at concentration 6.65 ±0.44 µM (determined by CV method) and 7.30 ±0.26 µM (determined by MTT method). The differential staining method shows that this inhibitor causes a cytotoxic effect. Conclusion : The results of these experiments indicate that autocrine growth of RMS cells is regulated by at least one autocrine loop, involving platelet-derived growth factor (PDGF) and its receptor (PDGFR). The fact that tyrphostin AG1296 is able to complete inhibition of RMS cell growth in vitro gives a chance for providing a new group of antitumor drugs, which may be more effective than the medicines used so far.